The Correlation between school principal leadership competence and teachers’ social behaviours - BURHANUDDIN YASIN; FAISAL MUSTAFA (Indonesian Research Journal in Education |IRJE|, 2020)
It has been predicted that the leadership competence of school principals indirectly influences the achievements of students because it has a positive impact on the social behaviour of their teachers. However, the correlation between those variables has not been supported by data. This research was therefore aimed at finding evidence for any correlations between the leadership competence of principals and the social behaviour of teachers under them. The samples were selected randomly, resulting in the selection of 110 EFL teachers in the Province of Aceh, Indonesia. The data for this study were collected using two questionnaires, a questionnaire about the social behaviour of teachers and a questionnaire rating the leadership competence of school principals. The data were analyzed using the Spearman correlation formula at significance level of 0.05. The results showed that almost all the constructs for leadership competence of principals were correlated to all the constructs of social behaviour of teachers at low level (0-0.29, p-value < 0.05) and moderate level (0.30 – 0.49, p-value < 0.05) of correlation. It was unexpected that teachers’ punctuality and accountability was not well-correlated to leadership competence of principals (p-value > 0.05). Based on the research results, it is recommended that the recruitment of school principals involve a standardized test consisting of all constructs of leadership competence.